Analisis Capaian Pembelajaran Kurikulum Merdeka pada Materi Asam Basa - Wulan, Wulan (TSAQOFAH, 2024)
Changes in the curriculum cause changes in the preparation of learning tools, one of which is about learning outcomes. Learning outcomes are abilities obtained through internalization of knowledge, attitudes, skills, competencies and accumulated work experience. This article attempts to provide an overview of the material content in the chemistry subject on the topic of acids and bases, guided by university books and Ministry of Education and Culture books in accordance with learning outcomes. Literature study is the method in this research by collecting data through online media, articles and books relating to chemistry learning outcomes in the Independent Curriculum. Data collection techniques are carried out by distinguishing, organizing and finding implied messages. Analysis of learning outcomes produces learning objectives, flow of learning objectives, and content of chemistry material on the topic of acids and bases that will be studied by students. To see the consistency in this research, a reliability test was carried out by experts (lecturers). Based on the results of the research that has been carried out, it can be concluded that the third alternative is to create learning objectives in chemistry subjects. Because in chemistry learning outcomes there are two elements, namely chemical understanding and process skills.